EVALUASI DISTORSI HARMONISA TEGANGAN PADA SISTEM TENAGA LISTRIK DI RUMAH SAKIT PANTI WILASA CITARUM SEMARANG - Luqman Assaffat (MEDIA ELEKTRIKA, 2011)
One of the factors that affect power quality is harmonic distortion. Harmonic distortion is measured by the value of Total Harmonics Distortion, THD. THD of Voltage harmonics always be a guide to the basic values of the instantaneous waveform. The research on the evaluation of the voltage harmonic distortion of the power system for Hospital of Panti Wilasa Citarum Semarang is necessary, because the hospital has loads of medical equipment, which requires a voltage supply of good quality, so that the equipment can work with good performance without any equipment malfunctions. Evaluation of voltage harmonic distortion of the power system of Panti Wilasa Citarum Hospital Semarang performed on all three existing MDP. Evaluation results show that these three pieces of existing MDP has Harmonic voltage distortion is still below the limit allowed by the IEEE Standard.Key Words : Harmonics, THD, Harmonics Evaluation